Tumpek Bubuh dalam Perspektif Teo-Ekologi Hindu - Acyutananda Wayan Gaduh (Sphatika: Jurnal Teologi, 2020)
Currently there are many challenges faced by humans, one of which is environmental problems. There have been many environmental damages which ironically have been caused by humans themselves. Land damage, air pollution, water pollution, forest fires, and so on are disasters that arise from human mistakes and desire. As religious beings, humans are very obedient in carrying out worship, but often forget the existence of other people. The teachings of theo-ecology offer a solution by harmonizing the relationship between humans and their creators and each other. Theo-ecology teaches humans to treat nature equally with other God's creations. Even in Hindu theo-ecological teachings, nature is not only God's creation but the existence of Himself. God permeates all of creation so that is appropriate for humans to treat nature with love. This concept is applied by Balinese Hindus through the celebration of Tumpek Bubuh as a day for all kinds of plants. On Tumpek Bubuh day, humans build harmonious interactions with plants through religious rituals.